Juvenile hormone facilitates the antagonism between adult reproduction and diapause through the methoprene-tolerant gene in the female Colaphellus bowringi. (July 2016) - Liu, Wen; Li, Yi; Zhu, Li; Zhu, Fen; Lei, Chao-Liang; Wang, Xiao-Ping
Abstract: In insects, the process whereby juvenile hormone (JH) regulates short-day (SD)-induced reproductive diapause has been previously investigated. However, we still do not understand the mechanism by which JH regulates long-day (LD)-induced reproductive diapause. In this study, we use a cabbage beetle, Colaphellus bowringi, which is a serious pest of cruciferous vegetables in Asia capable of entering reproductive diapause under LD conditions, as a model to test whether JH regulates female reproductive diapause similar to the mechanism of SD-induced diapause. Our results showed that the JH analog (JHA) methoprene significantly induced ovarian development but inhibited lipid accumulation of diapause-destined adults. Meanwhile, the transcripts of the vitellogenin ( Vg ) genes were upregulated, whereas the expression of the fat synthesis and stress tolerance genes were downregulated. RNA interference of the JH candidate receptor gene methoprene-tolerant ( Met ) blocked JH-induced ovarian development and Vg transcription, suggesting a positive regulatory function for JH-Met signaling in reproduction. Furthermore, under reproduction-inducing conditions, Met depletion promoted a diapause-like phenotype, including arrested ovarian development and increased lipid storage, and stimulated the expression of diapause-related genes involved in lipid synthesis and stress tolerance, suggesting JH-Met signaling plays an important role in the inhibition of diapause. Accordingly, our data indicate that JH acts through Met to facilitate development of the reproductive system by upregulating Vg expression while inhibiting diapause by suppressing lipid synthesis and stress tolerance in the cabbage beetle. Combined with previous studies in SD-induced reproductive diapause, we conclude that JH may regulate female reproductive diapause using a conserved Met-dependent pathway, regardless of the length of the photoperiod inducing diapause in insects. Graphical abstract: Highlights: JH promotes short-day-induced female reproduction via Met in Colaphellus bowringi . JH inhibits lipid storage and stress tolerance via Met to block long-day-induced adult diapause. JH-Met signaling facilitates the antagonism between adult reproduction and diapause. JH regulates photoperiodic reproductive diapause through a conserved Met-dependent pathway in insects.